Community radio for change and development - Fraser, Colin; Restrepoestrada, Sonia (2002)
Colin Fraser and sonia Restrepo-Estrada illustrate the role of a radio station, owned and run by a community, in providing the forum for the participatory, public dialogue which is essential for social change. The radio station is a platform for identifying and analysing problems and their solutions, thereby determining development inputs that truly meet local needs. Open access to on-air complaints from the audience can pressure local authorities to adopt practices of good governance and transparency. Cheap and easy to install and operate, community radio can also be the interface between poor communities and the internet. - Reproduced.
Keywords: Social change; Good governance; Communication; Electronic mail